Construction site : Firefight! - Rinker, Sherri Duskey (Rinker, Sherri Duskey. Goodnight, goodnight, construction site (Series), 2026)
When strong winds knock over electric lines and spark a dangerous blaze, fire engines team up with the Construction Site friends to save the day.